Morphological and Microscopical Characteristics of Oxalis corniculata L. - Loi, Vu Duc; Thi Nguyet, Le; Thi Hong Duong, Le; Thi Mai, Nguyen; Thuc Thu Huong, Nguyen; Thi Minh Hai, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 1DO - 10.25073/2588-1132/vnumps.4276, 2021)
This paper studies morphological and microscopical characteristics of Oxalis corniculata L. collected in Ha Tinh province (Vietnam). The paper identified the plant’s family as Oxalidaceae. Besides, the morphological characteristics and powder microscopy of the leaf and stem of Oxalis corniculata L. species were established. Specifically, the plant’s leaf and stem are characterized by pale yellow corolla, slightly pointed bracts and cube calcium oxalate crystals scattered in the soft tissue of the leaf; the herbal powder has twisted vascular grafts, unicellular hairs, among others. Keywords Oxalis corniculata , Oxalis corniculata L., Oxalis, Oxalidaceae, morphological characteristics, microscopical characteristics. References [1] D.H. Bich, D.Q. Chung, B.X. Chuong, N.T. Dong, D.T. Dam, P.V. Hien, V.N. Lo, P.D. Mai, P.K. Man, D.T. Nhu, N. Tap, T. Toan, Medicinal plants and animals in Vietnam, Volume I, Science and Technology Publishing House, Hanoi, 2004. (in Vietnamese) [2] M. Ibrahim, I. Hussain, M. Imran, N. Hussain, A. Hussain, T. Mahboob, Corniculatin A, a new flavonoidal glucoside from Oxalis corniculata, Revista Brasileira de Farmacognosia 23(4) (2013) 630-634. https://doi.org/10.1590/S0102- https://doi.org/10.1590/S0102695X2013005000059. [3] K.C. Oberlander, E. Emshwiller, D.U. Bellstedt, L.L. Dreyer, A model of bulb evolution in the eudicot genus Oxalis (Oxalidaceae), Molecular Phylogenetics and Evolution 51(1) (2009) 54–63. https://doi.org/10.1016/j.ympev.2008.11.022. [4] J. Zietsman, L.L. Dreyer, B. Jansen, V. Vuuren, Genetic differentiation in Oxalis (Oxalidaceae): A tale of rarity and abundance in the Cape Floristic Region, South African Journal of Botany, 75(1) (2009) 27–33. https://doi.org/10.1016/j.sajb.2008.06.003 [5] L.D. Bich, Good folk remedies, Ethnic Culture Publishing House, Hanoi, 2000 (in Vietnamese). [6] L.D. Bich, T.V. On, Botany, Medical Publishing House, Hanoi, 2007 (in Vietnamese). [7] D.T. Loi, Vietnamese medicinal plants and herbs, Medical Publishing House, Hanoi, 2005 (in Vietnamese). [8] N.V. Than, Laboratory of Medicinal Materials by microscopic method, Science and Technology Publishing House, Hanoi, 2003 (in Vietnamese).